Quantitative analysis of the morphological variation within the tiger beetle Calomera littoralis (Fabricius, 1787) (Coleoptera: Cicindelidae) in Mongolia - Shetterly, John A.; Duran, Daniel P. (Zootaxa, 2024)
For the past couple of centuries, much of tiger beetle taxonomic work has been focused on explaining intraspecific variation. In the Northern Hemisphere, over a thousand subspecies have been described and many have since been relegated to synonymy. Generally, the phenotypic-based subspecies circumscription has been purely descriptive. More quantitative and integrative analyses of the color and pattern variation in tiger beetles would be valuable. The geographically wide-ranging species, Calomera littoralis (Fabricius, 1987) contains 11 currently recognized subspecies, including two described from Mongolia that have been of questionable status due to the paucity of material available when they were described. Here, we assess the distribution of phenotypic variation within C. l. peipingensis (Mandl, 1934) and C. l. mongolensis (Mandl, 1981) to determine whether it best fits a pattern of two subspecies with a contact zone or a gradual cline, based on 494 specimens from 34 populations. Non-metric multidimensional scaling analyses and modeling of the fit between longitude and black dorsal phenotypes both indicate that the variation is best explained by a gradual cline of phenotype along an east-west gradient, not the presence of separate subspecies. As a result, we synonymize C. littoralis mongolensis, syn, nov. with C. littoralis peipingensis.